Use of an Endogenous Plasmid Locus for Stable in trans Complementation in Borrelia burgdorferi - Kasumba, Irene N. (Appl Environ Microbiol, 2015)
Targeted mutagenesis and complementation are important tools for studying genes of unknown function in the Lyme disease spirochete Borrelia burgdorferi. A standard method of complementation is reintroduction of a wild-type copy of the targeted gene on a shuttle vector. However, shuttle vectors are present at higher copy numbers than B. burgdorferi plasmids and are potentially unstable in the absence of selection, thereby complicating analyses in the mouse-tick infectious cycle. B. burgdorferi has over 20 plasmids, with some, such as linear plasmid 25 (lp25), carrying genes required by the spirochete in vivo but relatively unstable during in vitro cultivation. We propose that complementation on an endogenous plasmid such as lp25 would overcome the copy number and in vivo stability issues of shuttle vectors. In addition, insertion of a selectable marker on lp25 could ensure its stable maintenance by spirochetes in culture. Here, we describe the construction of a multipurpose allelic-exchange vector containing a multiple-cloning site and either of two selectable markers. This suicide vector directs insertion of the complementing gene into the bbe02 locus, a site on lp25 that was previously shown to be nonessential during both in vitro and in vivo growth. We demonstrate the functional utility of this strategy by restoring infectivity to an ospC mutant through complementation at this site on lp25 and stable maintenance of the ospC gene throughout mouse infection. We conclude that this represents a convenient and widely applicable method for stable gene complementation in B. burgdorferi.